Investigating a role for telomeric transcription in cancer - Dunkley, S (2018)
A constitutive hallmark of cancers is the extension of telomeric DNA. Approximately 85% of cancers extend their telomeres through the upregulation of the enzyme telomerase; whereas the remaining proportion use a recombination-based method known as Alternative Lengthening of Telomeres pathway (ALT). Tumours that exhibit the so-called ‘ALT’ pathway include: pancreatic neuroendocrine tumours, astrocytoma and osteosarcoma. The prognosis for many of these tumours is poor and the development of novel therapies is therefore an important unmet need. Recent work has shown, however, that ALT cancer cells exhibit some characteristic hallmarks which include; a near universal loss of the chromatin remodelling factor ATRX and increases in the transcription of a long non-coding RNA from telomeres, denoted TERRA. This project aims to determine: a) do increases in TERRA transcription facilitate the ALT pathway and b) could targeting of the TERRA transcript be a viable therapeutic approach for the treatment of ALT cancers? Consistent with a role for TERRA in facilitating ALT we demonstrate that ALT positive cancer cells exhibit changes in the nuclear distribution of TERRA, with clear telomeric foci detectable via RNA-FISH. Furthermore, we demonstrate that the use of LNA GapmeR antisense oligonucleotides can be used as a strategy to deplete TERRA levels. Importantly depletion of TERRA correlated with a loss in C-circles, a major marker of an active ALT pathway. Future work will determine how this affects longterm viability and whether this provides potential for therapeutic intervention in ALTpositive cancers.